7
Q:

Find the quadratic equations whose roots are the reciprocals of the roots of 2x2+5x+3?

A)  3x2+5x+2=0   

B) 5x2+3x+2=0 

C) 3x2-5x-2=0   

D)  None



A) A B) B
C) C D) D

Answer:   A) A



Explanation:

The quadratic equation whose roots are reciprocal of 2x2+5x+3=0 can be obtained by replacing x by 1/x.

 

Hence, 2(1/x)(1/x)+ 5(1/x) + 3 = 0

 

=> 3x2+5x+2=0

 

 

Q:

5068 / 37 x 4 = ?

A) 548 B) 625
C) 214 D) 745
 
Answer & Explanation Answer: A) 548

Explanation:

? = 5068 x 4/37

? = 548

Report Error

View Answer Workspace Report Error Discuss

1 8
Q:

X2+X2 =

A) 4X B) 2X
C) 2X^2 D) X/2
 
Answer & Explanation Answer: C) 2X^2

Explanation:

Here the given expression, 

X2 + X is an algebraic expression. Here in this expression the terms are like terms. Now to add them, add their coefficients.

Here in the given expression, the like terms are two X

Hence, adding their coefficients i.e, 1 + 1 = 2

Therefore, 

 

X2 + X2 = 2X2.

Report Error

View Answer Workspace Report Error Discuss

0 217
Q:

5x - 6 = 3x - 8

Solve the above equation.

A) 2 B) -1
C) -2 D) 1
 
Answer & Explanation Answer: B) -1

Explanation:

Given 5x - 6 = 3x - 8

5x - 3x = -8 + 6

2x = -2

=> x = -1.

Report Error

View Answer Workspace Report Error Discuss

2 364
Q:

3 x 3 + 3 - 3 + 3 = ?

A) 9 B) 12
C) -3 D) 3
 
Answer & Explanation Answer: B) 12

Explanation:

Using BODMAS law,

3 x 3 + 3 - 3 + 3 =

3 x 3 = 12

= 12 + 3 - 3 + 3

=  9 + 3

= 12

 

Hence, 3 x 3 + 3 - 3 + 3 = 12.

Report Error

View Answer Workspace Report Error Discuss

4 377
Q:

What is x squared plus x squared?

A) 4x B) 2x^2
C) x^4 D) 2x
 
Answer & Explanation Answer: B) 2x^2

Explanation:

In an algebraic expression, like terms are terms that contain the same variables raised to the same powers. Calculating x-squared plus x-squared is a matter of combining like terms. 

Now x^2 + x^2 = 2x^2

 

Hence, x-squared plus x-squared is equal to 2 times x squared.

Report Error

View Answer Workspace Report Error Discuss

1 330
Q:

What is 7 + 7 ÷ 7 + 7 × 7 - 7 =

A) 0 B) 42
C) 50 D) 57
 
Answer & Explanation Answer: C) 50

Explanation:

Given 7 + 7/7 + 7 x 7 - 7

By using BODMAS rule,

7 + 1 + 7 x 7 - 7

= 8 + 49 - 7

= 57 - 7

= 50.

 

Hence 7 + 7/7 + 7 x 7 - 7 = 50.

Report Error

View Answer Workspace Report Error Discuss

3 588
Q:

Find the Value of ?

5.112.2+5.553.3+6.31.4+7.22.001 = ? x 3.34

A) 81 B) 77
C) 73 D) 89
 
Answer & Explanation Answer: D) 89

Explanation:

This can be done in a method called Approximation.

Now, 

52 + 63 + 6 + 72 = ? x 3.3425 + 216 + 6 + 49 = ? x 3.34296 = ? x 3.34? = 2963.34 = 88.622  89 

Report Error

View Answer Workspace Report Error Discuss

7 550
Q:

Can you Solve 7 + 7 ÷ 7 + 7 x 7 + 7 - 7 ÷ 7 + 7 x 7 =

A) 112 B) 56
C) 0 D) 98
 
Answer & Explanation Answer: A) 112

Explanation:

7  + 7 ÷ 7 + 7 x 7 + 7 - 7 ÷ 7 + 7 x 7= 7 + 1 + 49 + 7 - 1 + 49= 8 + 56 + 48= 56 + 56= 112

Report Error

View Answer Workspace Report Error Discuss

9 473